Blood group O: A novel risk factor for increased postpartum blood loss?. Issue 4 (7th June 2018) - Kahr, M. K.; Franke, D.; Brun, R.; Wisser, J.; Zimmermann, R.; Haslinger, C.
Abstract : Introduction: Blood group O is known to be associated with lower levels of von Willebrand factor (VWF) and with increased bleeding complications. The influence of blood group O on postpartum blood loss was assessed by a few studies, however, without adjustment for important obstetric risk factors for postpartum blood loss. Aim: Aim of this study was to investigate whether women with blood group O exhibit increased blood loss after delivery in consideration of established risk factors for postpartum bleeding. Methods: A total of 1487 patients were prospectively included into this cohort study. Blood loss was assessed by estimated blood loss (in mL), and drop of haemoglobin (Δ haemoglobin) was calculated. Association of blood loss with risk factors (such as blood group O, cervical tears, morbidly adherent placenta, placenta praevia and uterine atony amongst others) was assessed with appropriate tests. Significant variables were entered into a stepwise multivariate regression analysis. Results: Women with blood group O showed a significantly higher blood loss when compared to women with blood group non‐O (529.2 mL ± 380.4 mL and 490.5 mL ± 276.4 mL, respectively, P = .024)). The increased blood loss in women with blood group O remained significant after multivariate regression analysis (difference 47 mL, P = .019). Conclusion: This is the first study reporting significantly increased blood loss following delivery in women with blood group O after adjustment for major risk factors for postpartum blood loss. Albeit having a statistically significant, but clinically minor effect on absolute blood loss, blood group O carriers may suffer from aggravated bleeding in the presence of additional obstetric bleeding pathologies.